The Tubarial Glands: Key Anatomical Features and Clinical Significance - Nur Aditya, Dwi Martha; Santosa, Winnie Nirmala; Marzuki, Jefman Efendi; Sukarno, Devitya Angielevi; Baharuddin, Baharuddin; Prawitasari, Dita Sukmaya; Sajuni, Sajuni; Setyo Wicaksono, Adhimas; Djuanda, Stephanie Natasha (Folia Medica Indonesiana, 2024)
Medical technological advancements have revealed previously unknown anatomical features in the nasal cavity known as tubarial glands. However, many questions remain unanswered concerning these glands. Through this systematic review, we sought to analyze the tubarial glands, including their major discovery, anatomical and histological features, and clinical significance. Articles were identified according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, with data collected from Scopus, ScienceDirect, SpringerLink, and PubMed until September 2024. Medical Subject Headings (MeSH) were utilized with various terminology: "tubarial gland*", "tubarial salivary gland*", and "radiotherapy”. The inclusion criteria were: (1) resources categorized as original research reports, case reports, case studies, letters to the editor, brief communications, commentaries, editorials, and news; (2) publications with accessible full text; and (3) articles providing information on the tubarial glands. The exclusion criteria were: (1) papers categorized as systematic reviews, meta-analyses, or bibliometric analyses; and (2) articles not published in English. The identification yielded 37 resources from around the world, including 19 original research reports (51.3%), 3 case reports (8.1%), 6 letters to the editor (16.2%), 2 brief communications (5.4%), 7 commentaries (18.9%), 1 editorial (2.7%), and 1 news article (2.7%). The research subjects comprised 1 healthy patient (2.7%) out of 26 subjects, 12 prostate cancer patients (32.4%) out of 612 subjects, 3 head and neck cancer patients (8.1%) out of 38 subjects, 1 nasopharyngeal carcinoma patient (2.7%) out of 240 subjects, 1 Sjögren's syndrome patient (2.7%) out of 29 subjects, 1 patient with oncocytic papillary cystadenoma (2.7%), and 20 patients with other conditions (54.0%). This systematic review suggests that the newly discovered glands exhibit similar morphological, histological, and physiological properties to salivary glands and may have a function in the lubrication and maintenance of the upper airway.